Pemeriksaan Awal Golongan Darah dalam Sarana Pencegahan Terjadinya Inkompatibilitas ABO pada Perempuan Usia Produktif di Kelurahan Krendang, Jakarta Barat - Christian Wijaya; Alexander Halim Santoso; Tizander Mayvians; Edwin Destra; Fransiska Iriani Rosmala Dewi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
ABO incompatibility is a medical condition that occurs when the mother’s blood type differs from the fetus she is carrying, potentially triggering immunological reactions harmful to both the mother and the fetus. This condition poses a significant risk in pregnancy and blood transfusions. Therefore, early blood type screening is essential for women of reproductive age as a preventive measure against ABO incompatibility. The education and blood type screening program was implemented using the Plan-Do-Check-Act (PDCA) approach, involving education, blood type screening, and evaluation. Through early detection and health education, women of reproductive age can better understand the risks of ABO incompatibility and take appropriate preventive actions. Proper education and regular screening can reduce pregnancy complications caused by ABO incompatibility and increase awareness among women of reproductive age about the importance of maintaining reproductive health. Early blood type screening plays a crucial role in preventing ABO incompatibility, thereby minimizing the risk of pregnancy complications in women of reproductive age.